APPROXIMATE ADOMIAN SOLUTIONS TO THE BRIGHT OPTICAL SOLITARY WAVES OF THE CHEN-LEE-LIU EQUATION - Mohammed, A S H F; Bakodah, H O; Banaja, M A (MATTER: International Journal of Science and Technology, 2019)
The present paper examines the Chen–Lee–Liu (CLL) equation numerically. The equation is an important type of the Derivative Nonlinear Schrodinger (DNLS) equations that describe the propagation of pulse in optical fibers. The optical solitary wave solutions of the CLL equation comprises of the recently obtained bright solitons via ansatz method. However, in this paper, we employ the promising Adomian Decomposition Method (ADM) to further demonstrate its efficiency in solving different types of Schrodinger equations. The method reveals amazing approximate solutions with minimal error as shown in the respective comparison tables and various plots depicted.